Analisis Peran Kader Posyandu dalam Upaya Pemasaran Sosial Kesehatan Gigi dan Mulut di Kelurahan Bukit Lama Kecamatan Ilir Barat I Palembang Tahun 2020 - Mujiyati, Mujiyati; Syahniati, Tri (Poltekkes Kemenkes Yogyakarta, 2021)
In increasing the healtht of teeth and mouth in society of Indonesia should have done because it is important to do it , as it is still in high risk indonesia , so that's why we try to do many things to increase the quality of society life. The cadre role is very important to do in doing the activities of integrated health care center , the Skills of Cadres counseling are one of the successful keys in serving systems in Health care center. The research has been done by doing some interviews to 10 cadres intensively as informan , the chief cadre and the chief of health care center as the key informan. The location of doing research is in Bukit lama sub-district in Ilir Barat 1 District.The Title of research is Analysis the integrated health care Cadre role in Social marketing efforts to the health of Mouth and Teeth in Bukit lama Sub-District in Ilir Barat 1 District. This Design research uses the methode of quaLitative study which is done by using the approach of rapid assestment procedure (RAP). This research is used the primery data. In collecting data we use Interview which is containg some questions list and voice recorder. The research purposes is to Analize the social cadre role in marketing to the community about the health of mouth and Teeth. The information from the Informant and Key-Informant is the responds to see how far the cadre role in giving information about the health Mouth and Teeth to the local communities. The Research Benefits is for Public Health Office Palembang city, health Centre Padang Selasa and Sub-District Ilir Barat I Palembang and the leader of Health center Office who has the same way and thinks in running the life of ntegrated Health centre